2020
DOI: 10.1093/cesifo/ifaa019
|View full text |Cite
|
Sign up to set email alerts
|

COVID: Not a Great Equalizer

Abstract: Coronavirus has been portrayed as the ‘great equalizer’. None seems immune to the virus and to the economic consequences of the lockdown measures imposed to contain its diffusion. We exploit novel data from two real-time surveys to study the early impact on the labor market of the lockdown in Italy—one of the two countries, with China, hit hard and early. We find that low-educated workers, blue collars, and low-income service workers were more likely to have stopped working both 3-week and 6-week after the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 13 publications
1
52
1
1
Order By: Relevance
“… Adams-Prassl et al (2020) shows that sectors such as arts and entertainment, education, food, accommodation and retail suffered in all countries considered in their study (United Kingdom, United States and Germany). The same occurred in Australia ( Churchill, 2020 ) and Italy ( Galasso, 2020 ). These are sectors in which women are over-represented, leading to a higher impact on their individual income ( Alon et al, 2020 ).…”
Section: Exploring the Social Impact Of Covid-19 Pandemics Under An Intersectional Perspectivementioning
confidence: 59%
See 2 more Smart Citations
“… Adams-Prassl et al (2020) shows that sectors such as arts and entertainment, education, food, accommodation and retail suffered in all countries considered in their study (United Kingdom, United States and Germany). The same occurred in Australia ( Churchill, 2020 ) and Italy ( Galasso, 2020 ). These are sectors in which women are over-represented, leading to a higher impact on their individual income ( Alon et al, 2020 ).…”
Section: Exploring the Social Impact Of Covid-19 Pandemics Under An Intersectional Perspectivementioning
confidence: 59%
“… Blundell et al (2020) demonstrated that in United Kingdom women, young and low-paid workers are those that suffered the most from the lockdown. In Italy, Galasso (2020) observed adverse effects on blue collars, low-educated workers and low-income services workers as well. Social distancing implied more significant job losses among ethnic minorities in the United States, especially Hispanics ( Béland et al, 2020 ; Montenovo et al, 2020 ).…”
Section: Exploring the Social Impact Of Covid-19 Pandemics Under An Intersectional Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…They identify significant sectoral differences which will in turn deepen existing inequities between and within countries. While initially the COVID‐19 pandemic was portrayed as the “great equalizer” and a virus that does not discriminate, work by Galasso (2020) highlights how low income, low educated and blue collar workers have suffered much worse labour market outcomes and suffered higher psychological costs relative to higher income‐individuals. In the Irish case, Crowley, Doran, and Ryan (2020) identified that COVID‐19 restrictions are likely to have unequal impacts across workers with younger, male, less educated, non‐nationals and the self‐employed more likely to find it difficult to work remotely and to practice social distancing in the workplace.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the severity and timing of the outbreak may explain part of the variation, several other factors have been pointed out as potential contributors (Frey et al, 2020). In particular, restrictive measures have been shown to hurt the economy (Pew, 2020), and distribute their burden unequally across the population (Galasso, 2020). In this scenario, elected leaders must often trade-off the advice of experts with the preferences of voters, who will ultimately judge their performance.…”
mentioning
confidence: 99%